Development and implementation of a trauma team education program in Georgetown, Guyana. Issue 7 (July 2021) - Ramirez, Rick; Cook, Courtney; Van Meter, Jessica
Abstract : Abstract: Trauma teams without structured team training demonstrate impaired team dynamics, which can cause delays in patient care, leading to poor patient outcomes. Improving team dynamics leads to better communication, reduced errors, and enhanced patient care. Evidence-based trauma team training was implemented and delivered within a resource-restricted ED. Abstract : Trauma teams without structured team training demonstrate impaired team dynamics, which can cause delays in patient care, leading to poor patient outcomes. Improving team dynamics leads to better communication, reduced errors, and enhanced patient care. Evidence-based trauma team training was implemented and delivered within a resource-restricted ED.